Enhanced bioavailability and relative distribution of free (unconjugated) curcuminoids following the oral administration of a food-grade formulation with fenugreek dietary fibre: A randomised double-blind crossover study. (April 2016) - Kumar, Dinesh; Jacob, Della; PS, Subash; Maliakkal, Abhilash; NM, Johannah; Kuttan, Ramadassan; Maliakel, Balu; Konda, Veera; IM, Krishnakumar
Highlights: Enhanced free curcuminoids oral bioavailability (>45×) with improved pharmacokinetics. Randomised double-blinded crossover study on largest number of subjects (n = 50). Relative distribution of free curcuminoids over conjugated metabolites in plasma. CGM provided >70% of the absorbed curcuminoids in unconjugated form. Formulation of curcumin with fenugreek galactomannans as curcumagalactomannosides (CGM). Abstract: Despite the various reports on enhanced bioavailable formulations of curcumin, systemic oral bioavailability of unconjugated curcuminoids remains a challenge. Considering the differences in plasma bioactivity and membrane permeability of free curcuminoids over conjugated metabolites, herein we report a randomised double-blinded crossover study (n = 50) to investigate the relative bioavailability and pharmacokinetics of free curcuminoids following the oral administration of high (1000 mg) and low (250 mg) doses of a food-grade formulation of curcumin with fenugreek dietary fibre as curcumagalactomannosides (CGM), which was reported to exhibit improved blood-brain – barrier permeability in rats. CGM administration provided over 45.5-fold enhancement in free curcuminoids bioavailability with improved pharmacokinetics when compared to unformulated standard curcumin. Further investigations with and without enzymatic hydrolysis of plasma collected over 5 h post-administration of CGM at 1000 mg dose revealed higher free curcuminoids in plasma (74 ± 8%) as compared to conjugated curcuminoids (26 ± 12%) indicating a significant distribution of free curcuminoids over conjugated curcumin metabolites.